Risk Perception and Vaccination Decision: Attitudes of Parents of Children Aged 6-12 Years towards COVID-19 Vaccination - Fauzan; Sukrang; Khairiyah, Mursyidah; Devi, Ratna; Sridani, Ni Wayan; Rahman, Abd; Arifuddin, Adhar; Nur, A Fahira (Public Health of Indonesia, 2025)
Background:The COVID-19 pandemic has highlighted the critical role of vaccination in mitigating the transmission of infectious diseases. However, parental attitudes toward COVID-19 vaccination are pivotal in determining the vaccination uptake among children. Understanding the factors that influence these attitudes is essential for the development of effective vaccination strategies. Objectives:This study aimed to identify the factors influencing parental attitudes toward COVID-19 vaccination in children aged 6-12 years. Methods:A cross-sectional study was conducted among parents of children aged 6-12 years. Data on parental attitudes toward COVID-19 vaccination, along with various demographic variables, were collected via structured interviews. Multivariate logistic regression analysis was utilized to identify significant predictors of parental attitudes toward vaccination. Results:The findings revealed several factors significantly associated with parental attitudes toward COVID-19 vaccination. Notably, perceptions regarding the halal status of the vaccine, family support, and parental anxiety were found to significantly influence these attitudes. Parents who considered the vaccine to be halal and who received strong family support were more likely to endorse vaccination. Conversely, higher levels of anxiety were negatively associated with vaccination support. Conclusions:These results highlight the importance of addressing perceptions regarding the halal status of the vaccine, enhancing family support, and alleviating parental anxiety to promote COVID-19 vaccination in children aged 6-12 years. Public health interventions should focus on providing clear, reliable information regarding vaccine halal status, fostering family discussions to encourage vaccination, and offering psychological support to reduce parental anxiety. These strategies are crucial for improving vaccination uptake and achieving herd immunity against COVID-19. Keywords:COVID-19 vaccination; parental attitudes; halal perception; family support; anxiety